Aestheticization of the self in social networks: human contradictions and contemporary subjective production - Marra e Rosa, Gabriel Artur (2016)
This paper analyzes the meanings attributed by social network users to the aestheticization of the self-phenomenon, product of the identities negotiation process among its participants. The objective is to join efforts to overcome the dichotomy established between disparate identity conceptions in the social network environment, and provide a concept that favors the operationalization of this category of studies. The study employed a qualitative methodology, conducting 16 semi-structured interviews with male and female Facebook users of diverse ages, ethnicities and socioeconomic levels; all residents in Brasilia-DF. A dialecticalsubjective production process among social network users was verified.